Developing Medicare Competitive Bidding: A Study of Clinical Laboratories - Hoerger, Thomas J. (CENTERS for MEDICARE & MEDICAID SERVICES, 1997)
Competitive bidding to derive Medicare fees promises several advantages over administered fee systems. The authors show how incentives for cost savings, quality, and access can be incorporated into bidding schemes, and they report on a study of the clinical laboratory industry conducted in preparation for a bidding demonstration. The laboratory industry is marked by variable concentration across geographic markets and, among firms themselves, by social and economic heterogeneity. The authors conclude that these conditions can be accommodated by available bidding design options and by careful selection of bidding markets.